Investigation of 980-nm diode laser parameters for soft tissue surgery - Korkmaz, Yusuf. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2006., 2006)
Within 800 - 1064 nm spectrum 980 nm diode laser is very important because ofthe local absorption peak around 980 nm. This work was carried out to find the irradiation e irradiated with 980 nm diode laser. Coagulations were quantified interms of diameter and depth measurements. Laser beam was applied in two different modes: Continuous wave and modulated in 250 ms on/off and 50 ms on/off cycles. Carbonization threshold for each mode (CW or modulated) were found. Maximum irradiances and maximum energy densities were recorded. For best proposed doseshistological analyses performed and thermal alteration was observed. For modulated wave,the effect of the duration of the duty cycle was discussed. The comparison of tissue typeswas done and water content of each tissue was calculated by desiccation method. Maximum irradiances, maximum energy densities and water content were compared. Theresult of this research study is a step for understanding the characteristics of 980 nm diodelaser for soft tissue surgery.|Keywords: 980-nm diode laser, lamb, soft tissue, surgery, parameter, dose, histology
Keywords: Diodes, Semiconductor.